Analysis of health risk for children living in the areas of atmospheric air, polluted with sulfur dioxide emissions - Petrosian A.A. (Medičnì Perspektivi, 2015)
Nearly 20-30% of all respiratory disorders and 40 % of asthma cases are the outcomes of intensive ambient air pollution. This study analyzes asthmatic morbidity among children exposed to high levels of SO2 from industrial emissions. The results of the study showed that ambient SO2 levels were at Сmean=107±38 mkg/m3. It was revealed that 29176 children, which is 98% of the mapped child population within the city, were exposed to very high SO2 levels and lived in the zone of high health risk (HQ=1,6ч4,5). The prevalence of the disease was estimated at 100 cases per 10,000 of the population (95% CI; 87.5-111.5). It was revealed that children living in the zones of increased health risks attributed to SO2 are more likely to develop bronchial asthma than unexposed ones (1,99 OR; 95% CI (1,95-2,60), p<0,01). Over the city, SO2 exposure is responsible for 30.5% of asthma cases among the exposed children population.